MEC101: Introduction to Engineering / College of Engineering - UiTM, College of Engineering (2023)
This course covers the engineering profession in general and mechanical engineering in particular. Students will be introduced to the various disciplines in engineering and particularly mechanical engineering, basic problem solving methods, laboratory report writing and the use of computers in engineering solutions, engineering estimations and approximations, dimensions, units and unit conversions, and representation of technical information. Group work introduces students to working in a team to collectively undertake and complete the assigned tasks. The computational tools useful for solving engineering problems are covered in the practical sessions.